The short‐lived inhibitory effect of Brachiaria humidicola on nitrous oxide emissions following sheep urine application in a highly nitrifying soil. Issue 6 (27th October 2021) - Ma, Yan; Charteris, Alice F.; Loick, Nadine; Cardenas, Laura M.; Sha, Zhipeng; López‐Aizpún, María; Chen, Qing; Jones, Davey L.; Chadwick, David R.
Abstract: Background: Brachiaria humidicola (Bh) has the ability to produce biological nitrification inhibitors (NIs) and release NIs from the root to the soil. Aims: To compare the effects of growing Bh with Brachiaria ruziziensis (Br, which is not able to produce NIs) on soil nitrogen (N) dynamics, N gases and carbon dioxide (CO2 ) emissions and nitrifiers and denitrifiers following sheep urine application, a laboratory incubation was conducted in a He/O2 continuous flow denitrification system (DENIS). This incubation was conducted in the absence of light. Hence the measured effects of Bh and Br on N cycling were the residual effect of biological NIs released into the soil prior to the incubation and released via root death. Methods: The treatments were: (1) Bh with water application (Bh + W); (2) Bh with sheep urine (Bh + U); (3) Br with water application (Br + W); (4) Br with sheep urine (Br + U). Results: Results showed that soil NO3 – concentration increased significantly in the soil with sheep urine application after the incubation. Soil nitrous oxide (N2 O) and nitric oxide (NO) emissions increased immediately after the sheep urine application and peaked twice during the incubation. Cumulative emissions for the first peak were significantly lower from the Bh + U treatment (0.054 kg N ha –1 ) compared with the Br + U treatment (0.111 kg N ha –1 ), but no significant differences were observed in the total cumulative N2 O and NO emissions between the Bh + U and Br + U treatment at the end of the incubation. Sheep urine addition did not affect the AOA, nirS and nosZ gene copies, but significantly increased the AOB gene copies after the incubation. Conclusions: We conclude that the residual effect of Bh to mitigate N2 O emissions in a highly nitrifying soil is short‐lived.